Mini-Me: My Miniaturized Version – Mother-Daughter Fashion Trends - Zilberman, Elinor (Mabatim: Journal of Visual Culture, 2022)
This article examines the conditions that led to the rise of mother-daughter fashion, a trend that has gained significant popularity in recent years. Mother-daughter fashion combines the clothing and accessories of the mother with those of her daughter, thereby creating a coordinated style that unites their appearance. At times, the garments of the pair are entirely identical, rendering the daughter a miniature mirror image of the mother from head to toe; at other times, the coordination is expressed only through shared features of a common language design. Identifying this trend as a recurring phenomenon throughout the twentieth and twenty-first centuries makes it possible to trace the social and cultural transformations reflected in their evolution. By following the shifts in mother-daughter fashion, the article highlights broader social and value-based changes that directly impacted the status of women and the cultural perceptions that have shaped the institution of motherhood.